Pengaruh Disiplin Pegawai dan Sarana Prasarana Terhadap Kinerja Pegawai Melalui Penerapan Absensi Online Di Kantor Kecamatan Banjarbaru Selatan - Tukiyat, Irawanto; Saputra, Welli; Ayuningtyas, Ayuningtyas; Priono, Singgih (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2024)
This study aims to explore the effect of employee discipline and infrastructure facilities on employee performance at the Banjarbaru Selatan Subdistrict Office through the application of online attendance as a mediating variable. This study used quantitative research, the sample was set as many as 71 respondents. Data collection using questionnaires and documentation. While analyzing data using path analysis assisted by SmartPLS 3 software. The results showed that (1) There is a significant influence between Online Attendance (Z) on Employee Performance (Y); (2) There is a significant influence between Work Discipline (X1) on Online Attendance (Z); (3) There is a significant influence between Work Discipline (X1) on Employee Performance (Y); (4) There is a significant influence between Infrastructure Facilities (X2) on Online Attendance (Z); (5) There is a significant influence between Infrastructure Facilities (X2) on Employee Performance (Y); (6) There is a significant influence between Work Discipline (X1) on Employee Performance (Y) through Online Attendance (Z); (7) There is no significant influence between Infrastructure Facilities (X2) on Employee Performance (Y) through Online Attendance (Z).